Temperature, fluid content and rheology of localized ductile shear zones in subsolidus cooling plutons. (20th July 2020) - Ceccato, Alberto; Goncalves, Philippe; Pennacchioni, Giorgio
Abstract: Temperature and fluid content are critical parameters that control rock rheology and strain localization in the continental crust. Here, we determine by thermodynamic modelling the T ‐ M H 2 O of localized ductile shearing during cooling of three different granitoid plutons: the Rieserferner and the Adamello plutons in the Italian Alps, and the Lake Edison pluton in the Sierra Nevada—USA. Shear zones exploited precursor joints, associated veins and alteration zones. T ‐ M H 2 O and P − T phase diagram sections were computed with Perple_X in the system MnO−Na2 O−CaO −K2 O−FeO−MgO−Al2 O3 −SiO2 −H2 O−Fe2 O3 . The phase diagram sections show that the nucleation of the brittle precursors (joints, veins) occurred at T » 450°C at fluid‐saturated conditions. Localized ductile shearing likely occurred at temperature ranging between 420 and 460°C evolving from initially fluid‐saturated to fluid‐undersaturated conditions in a closed system. In this temperature range, granitoid rocks are potentially subject to a series of retrograde metamorphic reactions replacing the load‐bearing feldspars with weaker phyllosilicates. Metamorphic reactions occurred in spatial association with the precursory structures, leading to localized shearing. Decreasing temperature and fluid‐undersaturated conditions likely hampered progressive strain accommodation in shear zones by slowing down metamorphic reactions, thermally activated dislocation creep processes, fluid‐mediated deformation mechanisms and weakening mechanisms. Polyphase granitoid ultramylonite and mylonitic quartz veins have been affected differently by the fluid‐undersaturated conditions of the system, as consequence of different dominant deformation mechanisms and syn‐kinematic paragenesis during localized shearing. Localized ductile shearing in cooling plutons effectively occurs in a limited temperature range (420–460°C) in which the strain accommodation capacity of the shear zone is controlled by the negative feedback between the cooling rate, the kinetics of metamorphic reactions and deformation mechanisms, and the consumption of the limited amount of available fluids.